Video mapping: inquietações para uma poética - Moraes, Wilson Leite de (2014)
In this exploratory work, the main objective is to identify the poetic structuring of video mapping, in addition to its technical dimension, as a new form of contemporary expression. The focus is its capability to enchant. In the course of the research we tried to think the mapping from the study of texts on the subject, with special attention to the concepts encountered that define their main characteristics. Empirical studies included tests and the production of a narrative to develop reflections whose results were used for understanding the poetical potential of the video mapping projection. Were parallel, consulted some studies on immersion, agency, and transformation potential bases of structuring and enchantment that allows the perception of the mapping as a form of expression. During the work we present a proposal for a better definition of video projection mapping, from the existing concept and identified characteristics. In the end, from the reflections contained in the corpus of work, we present our perception of how it underlies the poetic structuring of video mapping